Analisa Tingkat Kepuasan Pelanggan Menggunakan Metode Servqual Dan Lexicon Based - Ahmad Syar; Nurhalizah Noor; Aida Indriani; Anto, Anto (Journal of Big Data Analytic and Artificial Intelligence, 2019)
Customer satisfaction can be achieved through delivering optimal service performance to customers. Excellent service is realized when a business can maintain and develop customer loyalty while continuously improving the quality of services provided. In the case of Trijaya Computer Store, there is currently no evaluation framework in place to assess service quality, making it difficult to gauge customer satisfaction. In this study, two methods are employed: the SERVQUAL method and the Lexicon-Based method. The SERVQUAL method is used to measure service quality and customer satisfaction based on the services provided, while the lexicon-based method identifies which variables within the service quality dimensions need improvement by analyzing the three highest negative opinion scores. The analysis using the SERVQUAL method reveals that the largest service quality gap occurs in the Tangibles dimension, with a gap score of -0.44, indicating that customer expectations in this dimension are significantly unmet, leading to dissatisfaction. In the lexicon-based sentiment analysis, the highest negative opinion scores are 21, 17, and 16, corresponding to variables V3, V6, and V2, respectively. These variables represent specific aspects of the service that need improvement at Trijaya Computer. The variable V6, which states that "Trijaya Computer employees can resolve issues in a timely manner," is particularly important, as it appears in the results of both methods, indicating that timely problem resolution is a key concern for customers and should be prioritized for improvement. By addressing these issues, Trijaya Computer can enhance its service quality and improve customer satisfaction.